A dual-reciprocity boundary element approach for solving axisymmetric heat equation subject to specification of energy - Ang, Whye-Teong; Ooi, Ean-Hin (Engineering analysis with boundary elements, 2008)
A dual-reciprocity boundary element procedure is presented for the numerical solution of an axisymmetric heat conduction problem subject to a non-local condition. The non-local condition specifies the total amount of heat energy stored inside the solid under consideration. An unknown control function (of time) which governs the temperature on a certain part of the boundary of the solid is to be determined in the process of solving the axisymmetric heat equation. To check the validity of the numerical procedure, specific problems with known exact solutions are solved.